2013
DOI: 10.1186/1750-1326-8-41
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous expression of FAD-linked PS1 impairs proliferation, neuronal differentiation and survival of adult hippocampal progenitors

Abstract: BackgroundAlzheimer’s disease (AD) is characterized by progressive memory loss and impaired cognitive function. Early-onset familial forms of the disease (FAD) are caused by inheritance of mutant genes encoding presenilin 1 (PS1) variants. We have demonstrated that prion promoter (PrP)-driven expression of human FAD-linked PS1 variants in mice leads to impairments in environmental enrichment (EE)-induced adult hippocampal neural progenitor cell (AHNPC) proliferation and neuronal differentiation, and have provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Genetic studies have identified a number of genetic risk factors for AD, including amyloid precursor protein (APP), presenilin 1 (PSEN1), apolipoprotein E (APOE), ATPbinding cassette, subfamily A, member 7 (ABCA7), phosphatidylinositol-binding clathrin assembly protein (PICALM), complement receptor 1 (CR1), clusterin gene (CLU), and bridging integrator 1 (BIN1) [3][4][5][6][7][8][9][10]. Recently, many groups reported the association between rare genetic variants of triggering receptor expressed on myeloid cells 2 (TREM2) and the risk for sporadic AD [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies have identified a number of genetic risk factors for AD, including amyloid precursor protein (APP), presenilin 1 (PSEN1), apolipoprotein E (APOE), ATPbinding cassette, subfamily A, member 7 (ABCA7), phosphatidylinositol-binding clathrin assembly protein (PICALM), complement receptor 1 (CR1), clusterin gene (CLU), and bridging integrator 1 (BIN1) [3][4][5][6][7][8][9][10]. Recently, many groups reported the association between rare genetic variants of triggering receptor expressed on myeloid cells 2 (TREM2) and the risk for sporadic AD [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Other Aβ-based therapies, such as immunotherapy and autophagic restoration, are being explored for AD as well (Lemere, 2013 ; Li et al, 2013 ). In addition to mice (Eimer and Vassar, 2013 ; Veeraraghavalu et al, 2013 ), other models have been investigated for AD studies (Mccoll et al, 2012 ; Do Carmo and Cuello, 2013 ), which help to elucidate the role of γ-secretase in pathogenesis. Recently, it has been suggested that a set of γ-secretase product peptides in the cerebrospinal fluid may serve as biomarkers for AD (Hata et al, 2012 ; Rosén et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a co‐culture model with neuronal progenitor cells, primary microglia from FAD PS1 mutant mice showed lower stimulation of (wild‐type) neuronal progenitor cells proliferation as compared to microglia from PS1 wild‐type cells, and this effect was associated with altered secretion of soluble factors by PS1 mutant microglia (Veeraraghavalu et al . ). Together, these studies indicate complex roles of γ‐secretase in the regulation of intracellular signal transduction pathways and functions of microglia (Fig.…”
Section: Implications Of γ‐Secretase In Microglial Functionmentioning
confidence: 97%